Facing The Modern Era By Developing Digital Technology Innovation For Sustainable Green Tourism - Sari, Novita; Desfiandi, Andi; Santi, Faurani I; Saputra, Muhammad (International Journal of Artificial Intelligence Research, 2025)
Sustainable green tourism development is one of the priorities in supporting economic growth while preserving the environment. This study discusses the development of digital technology innovation in facing the modern era to support sustainable green tourism. In an increasingly digitalized global context, the tourism sector must adapt to technology to improve operational efficiency and minimize negative impacts on the environment. This study uses a qualitative approach by analyzing cases of technology implementation in various environmentally friendly tourist destinations in Indonesia. The results of the study show that the use of technology such as IoT-based management systems, digital promotions, and real-time data analytics contribute significantly to reducing carbon footprints and energy efficiency. However, challenges such as lack of digital infrastructure and limited technological literacy still need to be overcome. This study offers important insights for stakeholders to formulate innovative strategies that integrate technology to create sustainable and environmentally friendly tourism.